Analisis Kesulitan Siswa dalam Menyelesaikan Soal Eksponen Ditinjau dari Gaya Belajar Siswa - Sri Mulyani; Abdul Rahman; Rosidah; Fajar Arwadi (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This study aims to describe students' difficulties in solving exponential problems in terms of student learning styles. The type of research used is qualitative research. There are 6 research subjects, namely two students with visual learning style, two students with auditory learning style, and two students with kinesthetic learning style. Data collection techniques in this study are questionnaires, tests and interviews. The instruments used are learning style questionnaires, exponential mathematical ability tests, and interviews. The results showed that students with visual learning styles had fewer difficulties in understanding concepts, applying principles and stages of arithmetic operations. Students with auditory learning style have more difficulty in understanding concepts, applying principles and stages of arithmetic operations. Students with kinesthetic learning style have less difficulty in understanding concepts while more difficulties in applying the principles and stages of arithmetic operations.